Subliminal Emotional Faces Elicit Predominantly Right-Lateralized Amygdala Activation: A Systematic Meta-Analysis of fMRI Studies - Dahlén, Amelia D.; Schofield, Aphra; Schiöth, Helgi B.; Brooks, Samantha J. (Frontiers in Neuroscience, 2022)
Prior research suggests that conscious face processing occurs preferentially in right hemisphere occipito-parietal regions. However, less is known about brain regions associated with non-conscious processing of faces, and whether a right-hemispheric dominance persists in line with specific affective responses. We aim to review the neural responses systematically, quantitatively, and qualitatively underlying subliminal face processing. PubMed was searched for Functional Magnetic Resonance Imaging (fMRI) publications assessing subliminal emotional face stimuli up to March 2022. Activation Likelihood Estimation (ALE) meta-analyses and narrative reviews were conducted on all studies that met ALE requirements. Risk of bias was assessed using the AXIS tool. In a meta-analysis of all 22 eligible studies (merging clinical and non-clinical populations, whole brain and region of interest analyses), bilateral amygdala activation was reported in the left (x = −19.2, y = 1.5, z = −17.1) in 59% of studies, and in the right (x = 24.4, y = −1.7, z = −17.4) in 68% of studies. In a second meta-analysis of non-clinical participants only (n = 18), bilateral amygdala was again reported in the left (x = −18, y = 3.9, z = −18.4) and right (x = 22.8, y = −0.9, z = −17.4) in 56% of studies for both clusters. In a final meta-analysis of whole-brain studies only (n=14), bilateral amygdala was also reported in the left (x = −20.2, y = 2.9, z = −17.2) in 64% of studies, and right (x = 24.2, y = −0.7, z = −17.8) in 71% of studies. The findings suggest that non-consciously detected emotional faces may influence amygdala activation, especially right-lateralized (a higher percentage of convergence in studies), which are integral for pre-conscious affect and long-term memory processing.